Petanque Training Program Development for East Java Athletes in Preparation for the XXI Aceh-Sumut Pre-National Games (PRA PON) - Putri Faradilah; Nurhasan Nurhasan; Muchamad Arif Al Arha; Kolektus Oky Ristanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article and research aim to develop a training program focused on shooting and pointing techniques for East Java athletes in preparation for the upcoming Aceh-Sumut XXI Pre-National Sports Week (PRAPON). Shooting techniques are a fundamental skill in petanque, essential for scoring points and displacing the opponent’s ball from the jack. Meanwhile, pointing involves throwing techniques aimed at positioning the ball close to the jack. This study involved East Java Puslatda athletes undergoing regular training sessions as preparation for PRAPON Aceh-Sumut XXI. The method used in this study is Research and Development (R&D). The findings demonstrate that the developed training program can enhance the quality of East Java athletes’ shooting and pointing techniques, thereby aiming to achieve optimal results at PRAPON Aceh-Sumut XXI.